Effect of Temperature and Electric Field on Demulsification of Water-Oil Emulsion - Hosseini, M.; Ghaffar Ebadi, Abdol (Asian Journal of Chemistry, 2010)
In this work, desalting and dehydrating of crud oil in water-in-oil emulsion type is investigated under non-uniform electrical field using direct current (DC) and the results are compared with the ones of available methods. The effect of time, temperature and voltage on separation efficiency is also considered. The results show that the inhomogeneous electrical field method can be the proper and suitable way to desalt and dehydrate the water-in-oil emulsions. In laboratory conditions of 8000 to 10000 volts of voltage at 50 ºC the separation efficiency of 96 % is achieved.